2014
DOI: 10.3126/init.v5i0.10268
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Status and Conservation Initiatives of Red Panda Ailurus fulgens (Cuvier, 1825) in Nepal

Abstract: The existing status of Red Panda Ailurus fulgens in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Observation of tree stumps (105.27/ha) and looped trees (135.16/ha) shows active deforestation and habitat degradation around these herder sheds. The dogs these herders use to guard their livestock sometimes kill red pandas and other associated wildlife [ 43 , 44 , 45 ]. The transfer of livestock diseases to red pandas is also a danger [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observation of tree stumps (105.27/ha) and looped trees (135.16/ha) shows active deforestation and habitat degradation around these herder sheds. The dogs these herders use to guard their livestock sometimes kill red pandas and other associated wildlife [ 43 , 44 , 45 ]. The transfer of livestock diseases to red pandas is also a danger [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broadleaved open/closed forests, needle-leaved open/ closed forests were extracted from the land cover map of Nepal (Uddin et al 2015). Although, sightings from lower elevations have also been recorded (e.g., at 2,210 m in Ilam, eastern Nepal; Bista et al 2013), we used the elevation range of 2,800-3,900 m considering the sighting ranges of Red Panda in LNP. Preferred aspects (West, north, north-east, north-west) were extracted from the aspect map prepared out of the DEM using a surface analysis tool in GIS.…”
Section: Methodsmentioning
confidence: 99%
“…A similar study conducted in eastern and central Nepal showed the forests dominated by Betula utilis, Rhododendron spp., and Abies spp. with bamboo in the understory to be the most preferable plant species by the Himalayan Red Panda (Bista & Paudel 2013;Bista et al 2017).…”
Section: © Bhim Bahadur Shahimentioning
confidence: 99%